The Correlation between Hearing Loss and the Quality of Life of Workers Exposed to the Noise in the Textile Industry (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2019)
Noise is a stressor for hearing loss among workers. Unfortunately, hearing loss also affect workerâ€™s quality of life. This study aimed to investigate the correlation between hearing loss and quality of life among workers in textile industry. The study design was a cross-sectional survey.Â The study population were 200 workers exposed to the noisy textile industry. The data were analyzed using Spearman's rank correlation coefficient. The findings showed a significant relationship between hearing loss and the quality of life of the workers (rs=-0.698; p=0.000). The dimensions of quality of life associated with hearing loss were the Physical Functioning (rs=-0.493; p=0.000), Role-Physical (rs=-0.501; p=0.000), Bodily Pain (rs=-0.516; p=0.000), General Health (rs=-0.497; p=0.000), Vitality (rs=-0.527; p=0.000), Social Functioning (rs=-0.521; p=0.000), Role-Emotional (rs=-0.521; p=0.000), and Mental Health (rs=-0.517; p=0.000). This study concludes that hearing loss decreases the quality of life among workers exposed to the noise of the textile industry.